A qualitative study on overuse injuries: The beliefs of athletes and coaches - van Wilgen, C. P.; Verhagen, E. A. L. M. (Journal of Science and Medicine in Sport, 2012)
Objectives: Preventive approaches for overuse injuries in sports will be more successful when synchronised with athletes` and coaches` beliefs. We interviewed athletes and coaches in order to better characterize their beliefs about the definition of an overuse injury, as well as the intrinsic and extrinsic risk factors that underlie overuse injuries. Design: Qualitative study using in-depth interviews in athletes and coaches of different sports. Methods: Athletes who had experienced overuse injuries and coaches who trained athletes who had sustained overuse injuries from sports clubs were invited to participate through interview. We explored each participant`s individual definition of an overuse injury and the beliefs concerning the intrinsic and extrinsic risk factors concerning overuse injuries were explored. Results: After nine athletes and nine coaches, sample size saturation was confirmed. Athletes and coaches integrate somatic as well as psychological and sociological factors into the definition of and risk factors for overuse injuries. Intrinsic factors for an overuse injury were related to physical factors, technique, psychological factors and heredity. The extrinsic factors were related to situational, social and training factors, as well as the individual coach. Conclusions: Athletes and coaches have a holistic view on the definition of overuse injuries, and the intrinsic and extrinsic risk factors for overuse injuries. If preventive approaches for overuse injuries are developed and implemented, they should incorporate physical factors, as well as incorporate psychological and social factors. Based on the input of coaches and athletes, the latter are important risk factors for overuse injuries.